2017
DOI: 10.3389/fnins.2017.00172
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Endocytic Pathways for the Internalization of Exosome-Associated Oligomeric Alpha-Synuclein

Abstract: Misfolding and aggregation of alpha-synuclein (αsyn) resulting in cytotoxicity is a hallmark of Parkinson's disease (PD) and related synucleinopathies. The recent body of evidence indicates that αsyn can be released from neuronal cells by nonconventional exocytosis involving extracellular vesicles (EVs) such as exosomes. The transfer of αsyn between cells has been proposed to be an important mechanism of disease propagation in PD. To date, exosome trafficking mechanisms, including release and cell-cell transmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 57 publications
4
86
0
Order By: Relevance
“…Our results after introducing recombinant αSyn to the culture medium suggested that the Reportercells could reliably report the uptake of extracellular αSyn. Similar to other reports 75,77,78 , we did not detect direct cytoplasmic internalization of naked monomeric hαSyn by the Reporter-cells (derived from HEK293 cells). We rather observed that the cytosolic uptake required assistance with lipid-based elements as also had been shown in other studies 75,78 .…”
Section: Discussionsupporting
confidence: 92%
“…Our results after introducing recombinant αSyn to the culture medium suggested that the Reportercells could reliably report the uptake of extracellular αSyn. Similar to other reports 75,77,78 , we did not detect direct cytoplasmic internalization of naked monomeric hαSyn by the Reporter-cells (derived from HEK293 cells). We rather observed that the cytosolic uptake required assistance with lipid-based elements as also had been shown in other studies 75,78 .…”
Section: Discussionsupporting
confidence: 92%
“…Once internalized, exosomal a-Syn escapes the endosomal compartment and is targeted to the lysosome for degradation. Although receptor-mediated endocytosis has been proposed as a main route of exosome internalization, a more recent study using pharmacological inhibitors failed to confirm this (Delenclos et al 2017). According to this study, the entry of exosome-associated a-Syn in recipient H4 neuroglioma cells could be attributed neither to caveolin-mediated endocytosis nor macropinocytosis.…”
Section: The Case Of Exosomesmentioning
confidence: 99%
“…Recent evidence suggests that membrane binding is a crucial step for a-Syn internalization, which is mediated by Rab proteins (Masaracchia et al 2018). A recent study characterizing the internalization mechanisms of a-Syn containing exosomes found that the process was an active as opposed to a passive process, yet resistant to conventional blockers of both clathrin and caveolin-mediated endocytosis as well as micropinocytosis (Delenclos et al 2017). Clearly, the resolution of such discrepancies between methodological approaches will be required in the future.…”
Section: Mechanisms Of A-syn Internalizationmentioning
confidence: 99%